Comparison of human and animal hair - A microscopical analysis - S Nehal Safiya; Vishnu Priya Veeraraghavan; Abirami Arthanari; R Gayathri; J Selvaraj; S Kavitha; Y Dinesh (Wolters Kluwer Medknow Publications, 2022)
For nearly a century, hairs of animals and humans were employed in forensic research. It is found to be stable in certain environments, and thus, they are frequently retrieved at scenes of crime, and it is important to verify whether they are either human or animal. The present research was done at comparing the morphological differences among human hair and animal hair using a stereomicroscope. Samples of hair forming the outer coat of some autochthonous domestic and human remnants were evaluated in this study. Long strands of guard hair shaft were investigated by stereomicroscope accordingly. Microphotographs were taken in an iPad camera. The microscopic characteristics of cat hair samples showed the presence of small spikes on the surface, whereas the human hair sample showed a smooth appearance with no irregularities. The microscopic analyses of the human hair sample and cat hair sample under stereomicroscope suggest hair samples can be used as forensic evidence in crime scene investigation. The comparison of both the hair samples was done, and the differences were significantly evident.